Sunflower leaf senescence : a complex genetic process with economic impact on crop production - Moschen, Sebastian Nicolas; López Gialdi, Agustín I.; Paniego, Norma Beatriz; Fernandez, Paula del Carmen; Heinz, Ruth Amelia (2017)
Leaf senescence is a complex process controlled by multiple genetic and environmental variables. In different crops, a delay in leaf senescence has an important impact on grain yield trough the maintenance of the photosynthetic leaf area during the reproductive stage. In sunflower (Helianthus annuus L.), the fourth largest oil crop worldwide, senescence reduces the capacity of plants to maintain their green leaf area for longer periods, especially during the grain filling phase, leading to important economic losses. In crop species, taking into account the temporal gap between the onset and the phenotypic detection of senescence, identification of both, candidate genes and functional stay-green are indispensable to enable the early detection of senescence, the elucidation of molecular mechanisms and the development of tools for breeding applications. In this chapter a comprehensive literature revision of leaf senescence process not only in model plant species but also in agronomical relevant crops is presented. Results derived from system biology approaches integrating transcriptomic, metabolomic and physiological data as well as those leading to the selection and characterization of stay green sunflower genotypes are included, making an important contribution to the knowledge of leaf senescence process and providing a valuable tool to assist in crop breeding.